Assessment of the antioxidant and antimicrobial activity of hydrolysates from lupine (Lupinus mutabilis) flour - Sara Gallegos Bosmediano; José Villacís-Chiriboga; Yadira Quimbita Yupangui; Fernanda Guimaraes Drummond e Silva; Jenny Ruales Nájera (The Journal of Engineering and Exact Sciences)
Lupine (Lupinus mutabilis) is a seed commonly used as a staple food in the Mediterranean region and South America, particularly in Ecuador, where it has been consumed for centuries. Known for its high protein content (45%), lupine could serve as an important source for producing protein isolates, concentrates, and hydrolysates with bioactive capacities. To address this potential, our research aimed to evaluate the effect of the type of flour and hydrolysis conditions (enzyme and time) on the antioxidant and antimicrobial capacities of lupine hydrolysates. Thus, two types of flour were prepared: raw flour (RF) and debittered and defatted flour (DDF). Subsequently, enzymatic hydrolysis was conducted using three different enzymes (pancreatin, papain, and endopeptidase), and the hydrolysates were collected at various time points: 4 and 48 hours. Antioxidant capacity was assessed using the Oxygen Radical Absorption Capacity (ORAC) test and the Ferric Reducing Antioxidant Power (FRAP) test. Additionally, antimicrobial capacity was evaluated by measuring the inhibition of Staphylococcus aureus and Escherichia coli. The results showed hydrolysates treated with pancreatin at 4 hours from raw flour exhibited the highest antioxidant capacity, while debittered and defatted hydrolysates treated with pancreatin at 48 hours demonstrated the highest antimicrobial capacity. Overall, these findings highlight lupine as a valuable source for obtaining hydrolysates with antioxidant and antimicrobial properties. Furthermore, the type of flour and hydrolysis conditions (enzyme and time) significantly affected the bioactive capacities.